Study of Psychological Satisfaction of Population with Services of the Primary Health Care Integrated into Public Health - Yessimov, Nabi; Izmailova, Nailya; Yessimov, Dauletkhan (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The article aims to examine public opinion to achieve a synergistic effect and thereby integrate primary patient feedback in the organization of the promotion of primary care and public health. The leading method to the study of this problem is the questionnaire survey that has afforded revealing issues of regulation of primary and public health care, and in particular, the state of the psychological attitude of patients to primary health care integrated into the public health system of the Republic of Kazakhstan. In order to study the organization of the Primary Health Care System integrated into Public Health Service, 400 healthcare workers were questioned. The authors also analyzed socio-psychological factors that affect the quality of the provision of qualified primary health care. The practical novelty of the study is that the organization of the synergic system of primary health care and public health is implemented based on the public administration system and local systems of public health evaluation. It was concluded that it is more expedient to build a system of integration of primary health care and public health based on feedback from the people and a formation of a spatially distributed network of public medical organizations, which will reduce the burden on, particularly busy areas.